Reproducing the three-dimensional structure of a tRNA molecule from structural constraints. - Major, F (1993)
The three-dimensional structure of yeast tRNA(Phe) was reproduced at atomic resolution with the automated RNA modeling program MC-SYM, which is based on a constraint-satisfaction algorithm. Structural constraints used in the modeling were derived from the secondary structure, four tertiary base pairs, and other information available prior to the determination of the x-ray crystal structure of the tRNA. The program generated 26 solutions (models), all of which had the familiar "L" form of tRNA and root-mean-square deviations from the crystal structure in the range of 3.1-3.8 A. The interaction between uridine-8 and adenosine-14 was crucial in the modeling procedure, since only this among the tertiary pairs is necessary and sufficient to reproduce the L form of tRNA. Other tertiary interactions were critical in reducing the number of solutions proposed by the program.